FORECASTING OF SATISFACTION AND REVISIT INTENTION OF INDONESIA SHOPPERS IN SHOPPING MALLS - Risca Fitri Ayuni (Universitas Mercu Buana, 2017)
Abstract. Due to tight competition, changing value proposition of customer and shiftingof mall functions become center for leisure purposes, shopping mall developer mustfocus on create shopper satisfaction to influence their post-transaction behaviors. Thisstudy investigates the relationship between mall personality, self-congruity, perceivedquality, shopping value, shopper satisfaction and revisit intention. Two hundredrespondents participated in this study. In order to achieve the aim of this study, SPSS23 and PLS 3 were used. Out of the 15 hypotheses proposed, ten are supported. Aspredicted, mall personality, self-congruity, perceived quality significantly have asignificant effect on shopping value and shopper satisfaction (except perceived qualityhas no effect on shopping value). The findings show that Mall Personality is predictiveof Self-Congruity and Perceived Quality; while Shopping Value can be used to predictShopper Satisfaction. The result indicated that Perceived Quality is not statisticallysignificant affect on Shopping Value. Moreover, Self-Congruity has significant affecton Perceived Quality. In addition, Mall personality, Self-Congruity and PerceivedQuality are not good predictors of Revisit Intention. Finally, the result confirms thatShopper Satisfaction and Shopping Value have a significant effect on Revisit Intention.